The effect of aspirin on bleeding after extraction of teeth - Nasser Nooh (Saudi Dental Journal)
Acetylsalicylic acid (ASA) generically known as aspirin is used clinically as an analgesic, antipyretic, anti-inflammatory and as a medication to prevent platelet aggregation. Many studies have investigated bleeding associated with ASA. Objective: The aim of this study was to determine if ASA was associated with bleeding after dental extraction. Patients and methods: One hundred and eighty-nine subjects were divided into four groups. Group 1A subjects who received ASA, underwent simple extraction. Group 1B subjects who received ASA, underwent surgical extraction. Group 2A subjects who did not receive ASA, underwent simple extraction which served as control group. Group 2B subjects who did not receive ASA, underwent surgical extraction which also served as control group. Results: The results showed that Group 1B was the only group which showed bleeding after 24 h. All groups had similar results after 48 h and 5 days post-operatively. Conclusion: The study concluded that subjects who received 81 mg ASA daily could undergo dental extraction without bleeding risks.